Buffalo Bill's Wild West celebrity, memory, and popular history - Kasson, Joy S. (Hill and Wang, 2000)
"Joy S. Kasson's book traces Cody's rise from scout to international celebrity, and shows how his image was shaped. Publicity stressed his show's "authenticity," yet audiences thrilled to its melodrama; fact and fiction converged in a performance that instantly became part of American tradition." "But how, precisely, did that come about? How, for example, did Cody use his audience's memories of the Civil War and the Indian Wars? He boasted that his show included participants in the recent conflicts it presented theatrically, yet he also claimed it evoked "memories" of America's bygone greatness. Kasson's shrewd, engaging study - richly illustrated - in exploring the disappearing boundary between entertainment and public events in American culture shows us just how we came to imagine our memories."--BOOK JACKET.